Design, analysis and modeling of a novel hybrid powertrain system based on hybridized automated manual transmission. (1st September 2017) - Wu, Guang; Dong, Zuomin
Highlights: A novel series-parallel hybrid electric powertrain system with a dedicated transmission design (US patent pending) compatible with strong HEV and PHEV platforms is presented. Detailed powertrain dynamics during various gearshift events are analyzed and summarized. The concept of torque-gap-filler for this system is also analyzed in depth, with one gearshift split as 7 sequential phases. Each of the 7 phases relies on dedicated control algorithm. A full vehicle model emphasizing the hybridized automated manual transmission (HAMT) is built in the MATLAB SIMULINK and SIMDRIVELINE environment. Details of the new HAMT design, including gearshift process and synchronizers, are also modeled to simulate torque-gap-filler feature. Control algorithms are built and tuned carefully to operate the powertrain system. Simulation results show that the control algorithm can successfully coordinate powertrain components to accomplish smooth gearshift and desirable drivability. This novel hybrid system not only avoided low-torque disadvantage of mainstream power-split system, but also improved the drivability of vehicle equipped with high-efficient AMT. The proposed HAMT and its controls present superior efficiency, performance and drivability. Abstract: Hybrid electric vehicles are widely accepted as a promising short to mid-term technical solution due to noticeably improved efficiency and lower emissions at competitive costs. In recent years, various hybrid powertrain systems were proposed and implemented based on different types of conventional transmission. Power-split system, including Toyota Hybrid System and Ford Hybrid System, are well-known examples. However, their relatively low torque capacity, and the drive of alternative and more advanced designs encouraged other innovative hybrid system designs. In this work, a new type of hybrid powertrain system based hybridized automated manual transmission (HAMT) is proposed. By using the concept of torque gap filler (TGF), this new hybrid powertrain type has the potential to overcome issue of torque gap during gearshift. The HAMT design (patent pending) is described in details, from gear layout and design of gear ratios (EV mode and HEV mode) to torque paths at different gears. As an analytical tool, mutli-body model of vehicle equipped with this HAMT was built to analyze powertrain dynamics at various steady and transient modes. A gearshift was decomposed and analyzed based basic modes. Furthermore, a Simulink-SimDriveline hybrid vehicle model was built for the new transmission, driveline and vehicle modular. Control strategy has also been built to harmonically coordinate different powertrain components to realize TGF function. A vehicle launch simulation test has been completed under 30% of accelerator pedal position to reveal details during gearshift. Simulation results showed that this HAMT can eliminate most torque gap that has been persistent issue of traditional AMT, improving both drivability and performance. This work demonstrated a new type of transmission that features high torque capacity, high efficiency and improved drivability.